The Portuguese version of the Hartford Geriatric Social Work Competency Scale II – assessment subscale: factor structure and psychometric properties - Daniel, F.; Monteiro, R.; Ferreira, J.; Ana Galhardo (Journal of Gerontological Social Work, 2019)
The current study aimed to test the fit of the Portuguese version of the Hartford Geriatric Social Work Competency Scale II – Assessment subscale (GSWCS-A) and explore its factor structure and psychometric properties in a sample of 534 social workers working in the gerontology field. Confirmatory factor analysis showed that all items presented good factor loadings and that the single-component model fit the data well. The GSWCS-A showed very good internal consistency. Despite the existence of different theoretical perspectives on Social Work, which frame the required competencies for professional practice, the GSWCS-A Portuguese version revealed similitudes with studies conducted in other countries. Nevertheless, the different factor structures (single-component vs. bi-factorial) may indicate that different competencies are being emphasised in terms of professional training. To sum, the GSWCS-A may be a short and useful self-report instrument for addressing social workers’ assessment competencies in the gerontology setting.